Tempohomes: Untersuchung sozial-räumlicher Aneignungspraktiken von Geflüchteten in ausgewählten Berliner Gemeinschaftsunterkünften (Universitätsverlag der Technischen Universität Berlin, 2022)
This report, a cooperation project between TU and LAF Berlin, documents everyday life and living in container villages and tempohomes in 2018 and presents the residents' perceptions and perspectives, their everyday life and their agency in dealing with everyday challenges. Through architectural ethnographic documentation and interviews, six selected locations were investigated by students of the TU Berlin. The insights gained are summarised in short thematic essays. The LAF introduction places the students' work in the context of the turbulent political and planning challenges of developing and building the sites in contemporary history. It concludes by reflecting on their significance for current and future accommodation strategies from the LAF's perspective.